Does forecast-based financing (FbF) lower women's vulnerability to flooding? - Fabiha Rahman; Shampa; Sonia Binte Murshed; Mashfiqus Salehin; Faisal Mahmud Sakib; Erin Coughlan de Perez (Progress in Disaster Science)
Forecast-based financing (FbF) is gaining traction globally in the humanitarian sector as a critical tool for reducing disaster risk. Global and national literature on FbF mainly shed light on the effectiveness in reducing household-level vulnerability without a particular focus on women's specific vulnerability. This study uses qualitative methods to analyze rural Bangladeshi women's riverine flood challenges and whether the FbF has reduced their vulnerability to flooding. The study was conducted in two distinct geographical settings in northern Bangladesh: Charland (river island) and Mainland, without flood embankment protection. The findings reveal that FbF cash assistance primarily aided rural women in reducing the financial vulnerability of their households. Spending the cash assistance on buying food and boat evacuation directly benefits women and men alike and reduces the need for taking loans. However, no spending was made on women's personal utility and safety needs before, during, and after the flood. Charland and Mainland females faced barriers to basic utility and hygiene services, with Charland women faring slightly better. Our findings suggest that existing rural socio-cultural norms, cash disbursement timing, and other factors influenced women's cash aid anticipatory action choices, and the humanitarian actors and recipients should coordinate to improve the situation.